Vascular Smooth Muscle Sirtuin-1 Protects Against Diet-Induced Aortic Stiffness. Issue 3 (September 2016) - Fry, Jessica L.; Al Sayah, Leona; Weisbrod, Robert M.; Van Roy, Isabelle; Weng, Xiang; Cohen, Richard A.; Bachschmid, Markus M.; Seta, Francesca
Abstract : Arterial stiffness, a major cardiovascular risk factor, develops within 2 months in mice fed a high-fat, high-sucrose (HFHS) diet, serving as a model of human metabolic syndrome, and it is associated with activation of proinflammatory and oxidant pathways in vascular smooth muscle (VSM) cells. Sirtuin-1 (SirT1) is an NAD + -dependent deacetylase regulated by the cellular metabolic status. Our goal was to study the effects of VSM SirT1 on arterial stiffness in the context of diet-induced metabolic syndrome. Overnight fasting acutely decreased arterial stiffness, measured in vivo by pulse wave velocity, in mice fed HFHS for 2 or 8 months, but not in mice lacking SirT1 in VSM (SMKO). Similarly, VSM-specific genetic SirT1 overexpression (SMTG) prevented pulse wave velocity increases induced by HFHS feeding, during 8 months. Administration of resveratrol or S17834, 2 polyphenolic compounds known to activate SirT1, prevented HFHS-induced arterial stiffness and were mimicked by global SirT1 overexpression (SirT1 bacterial artificial chromosome overexpressor), without evident metabolic improvements. In addition, HFHS-induced pulse wave velocity increases were reversed by 1-week treatment with a specific, small molecule SirT1 activator (SRT1720). These beneficial effects of pharmacological or genetic SirT1 activation, against HFHS-induced arterial stiffness, were associated with a decrease in nuclear factor kappa light chain enhancer of activated B cells (NFκB) activation and vascular cell adhesion molecule (VCAM-1) and p47phox protein expressions, in aorta and VSM cells. In conclusion, VSM SirT1 activation decreases arterial stiffness in the setting of obesity by stimulating anti-inflammatory and antioxidant pathways in the aorta. SirT1 activators may represent a novel therapeutic approach to prevent arterial stiffness and associated cardiovascular complications in overweight/obese individuals with metabolic syndrome. Abstract : Supplemental Digital Content is available in the text.